1992
DOI: 10.1128/aem.58.9.2730-2736.1992
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of toxic pyrrolizidine alkaloids from tansy ragwort (Senecio jacobaea) in ovine ruminal fluid under anaerobic conditions

Abstract: The ability of ovine ruminal fluid to metabolize pyrrolizidine alkaloid (PA) from Senecio jacobaea under anaerobic conditions was evaluated. Four fistulated sheep fed PA served as individual sources of ruminal fluid, which was incubated in a defined minimal salts medium under two different anaerobic conditions, denitrifying and methanogenic. Anaerobic cultures amended with ovine ruminal fluids (20%), PA (100 ,ug/ml), and a defined minimal salts medium were monitored for a period of several days. These cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…Resistance to PA poisoning was previously reported in sheep where the detoxification was hypothesised to occur in the rumen, suggesting that sheep rumen microorganisms have the ability to metabolise PAs and render them non-toxic [ 74 , 172 ]. Resistance against PA poisoning was reported to only occur in animals that were previously exposed to the toxin allowing rumen microbes to adapt to metabolise PAs.…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to PA poisoning was previously reported in sheep where the detoxification was hypothesised to occur in the rumen, suggesting that sheep rumen microorganisms have the ability to metabolise PAs and render them non-toxic [ 74 , 172 ]. Resistance against PA poisoning was reported to only occur in animals that were previously exposed to the toxin allowing rumen microbes to adapt to metabolise PAs.…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…A later study showed the synergistic relationship of ruminal microorganisms in metabolising S. jacobaea PAs. It was reported that a group of unidentified ruminal bacteria were responsible for PA metabolism while ruminal protozoa may have been involved in increasing the rate of degradation [ 172 ]. This could be due to the presence of protozoa and certain bacteria that could be responsible for the adsorption or adherence of PA-degrading bacteria to plant particles thus allowing the metabolising bacteria to utilise PAs [ 172 ].…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…The pyrroles originating from dehydrogenation of PAs can bind with the hepatocyte DNA, inhibiting cellular mitosis and thereby causing hepatic dysfunction [46, 47]. However, it is known that sheep, the targets of our study, are more resistant to Senecio intoxication than cattle due to their ruminal microbiota [48] and liver metabolization system [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some PA cause cirrhosis of the liver and some cause lung damage, leading to death (32). In the western United States, multimillion dollar livestock losses result from the poisoning of cattle and horses because of ingestion of tansy ragwort, Senecio jacobaea (10,11,34). Ingestion of plants which contain PA is also a worldwide problem, affecting animal and human populations, because of PA in various weeds, herbal remedies, and contaminated food and feed (17).…”
mentioning
confidence: 99%